Affiliation Oriented Journals: Don’t Worry About Peer Review If You Have Good Affiliation - Mehdi Dadkhah; Adel M. Alharbi; Mohammad Hamad Al-khresheh; Tole Sutikno; Tomasz Maliszewski; Mohammad Davarpanah Jazi; Shahaboddin Shamshirband (Institute of Advanced Engineering and Science, 2015)
There has been a growing concern about fraud peer review articles that have been published in some journals in favor of their authors' affiliation, which have been discussed extensively by some researchers. This research paper introduces a new another challenge in academic world concerning journals’ editors who look at authors' affiliations rather than papers' contents. In this short paper, we will introduce this alarming problem and do an experimental test by submitting computer generated papers to some journals and finally present the results of our experiment. The paper is an expression of our concern about providing for maximum high ethics in and quality of publication policy of modern scientific journals.